Identification of Instructional Practices according to Children’s Needs to Recognize Letters, Numbers, Concepts and Digits at Early Childhood Education - Rasheed, Muhammad Shahid; Shahid, Shahid Hussain; Zafar, Jam Muhammad (Annals of Human and Social Sciences, 2024)
The present study aims to identify the instructional practices according to children’s needs at early childhood education. Quantitative method was used for this survey and descriptive nature study. Population comprised of head teachers, teachers and children of ECE in district Rahim Yar Khan. Sample consisted of 120 head teachers, 240 care givers and 1200 children of ECE. The observation sheet was developed for data collection. Validaty and reliability of the tools were calculated through SPSS-23. The study concluded that majority of head teachers and teachers suggesting a generally positive attitude towards using objects for number recognition in early childhood education, majority of teachers indicated a general preference for using objects. This suggests a divergence in practices and the potential need for a more standardized approach in teaching digit recognition through objects in early childhood education. On the basis of results researchers recommended that, standardize the use of teaching methods, tailor instructional techniques to accommodate diverse learner needs, Develop guidelines to promote consistent implementation of interactive methods, and encourage the widespread adoption of supplementary tools like flashcards and drawing activities to reinforce concepts such as letter pronunciation and shape recognition.